The Effectiveness Of School Principal Management In Collaborating The Curriculum At SDIT Al-Khansa - Hidayat, Taufik; Mesiono, Mesiono; Rifa'i, Muhammad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Study This aim For give understanding deep about extent of the curriculum implemented in a way effective and how head school role in the integration process curriculum the . Additionally , research this will too reveal challenges and obstacles faced by management school in reach objective education , with hope results study This can give recommendation constructive For future improvements and development . Study This use approach descriptive qualitative For evaluate effectiveness management head school in integrate curriculum at SDIT Al-Khansa. Study This show that implementation The Independent Curriculum and Integrated Islamic Curriculum at SDIT Al-Khansa achieve progress significant with support from teachers, administration , and communications effective with parents . Although There is challenge like parent involvement , evaluation periodic and bait come back constructive help overcome problem . Head school active in evaluation and observation , as well ensure planning and implementation curriculum done systematic . Collaboration between head schools and teachers, as well routine coordination , strengthening implementation curriculum . Evaluation periodic and bait come back from all party proven crucial in increase effectiveness curriculum and quality learning